PERSEPSI MAHASISWA TERHADAP PEMBELAJARAN DARING SEBAGAI ALTERNATIF MODEL PEMBELAJARAN DI MASA COVID-19 - Aryanti Dwi Untari; Sunila Sunila (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2021)
ABSTRACT This research is entitled the perceptions of PPKn semester 6 students towards online learning as an alternative learning model during the Covid-19 period at Banten Jaya University in the 2019/2020 Academic Year. Faculty of Teacher Training and Education, Pancasila and Citizenship Education. This study aims to determine the perceptions of 6th semester PPKn students towards online learning as an alternative learning model during the Covid-19 period at Banten Jaya University for the 2019/2020 Academic Year. The subjects of this study were 20 PPKn students in semester 6 and 5 PPKn lecturers at Banten Jaya University. This research uses descriptive qualitative research methods. Qualitative research is a research procedure that describes a situation and symptoms that exist in the object to be studied. The results of this study indicate that the perception of 6th semester PPKn students towards online learning as an alternative learning model during the Covid-19 period is considered to have understood in online learning during the Covid-19 period. Students and lecturers assessed that the online learning process was going well by using the WhatsApp application, google classroom and Zoom as learning media. Keywords : Student Perception, Online Learning, Covid-19